2020
DOI: 10.1080/15476286.2020.1713539
|View full text |Cite
|
Sign up to set email alerts
|

NXF1 and CRM1 nuclear export pathways orchestrate nuclear export, translation and packaging of murine leukaemia retrovirus unspliced RNA

Abstract: Cellular mRNAs are exported from the nucleus as fully spliced RNAs. Proofreading mechanisms eliminate unprocessed and irregular pre-mRNAs to control the quality of gene expression. Retroviruses need to export partially spliced and unspliced full-length RNAs to the cytoplasm where they serve as templates for protein synthesis and/or as encapsidated RNA in progeny viruses. Genetically complex retroviruses such as HIV-1 use Rev-equivalent proteins to export intron-retaining RNA from the nucleus using the cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 59 publications
(45 reference statements)
1
19
0
Order By: Relevance
“…This increase over time of the Gag-gRNA ratio is probably related to the time-dependent increase in the concentration of the two partners ( 7 , 74 ). However, in agreement to the results obtained with MLV where 20% of particles were found containing viral RNA ( 80 ), these results indicate that the majority of the HIV viral particles lacks gRNA. These particles are not empty because they contain cellular RNAs ( 30 , 33 , 71 , 81 ).…”
Section: Discussionsupporting
confidence: 91%
“…This increase over time of the Gag-gRNA ratio is probably related to the time-dependent increase in the concentration of the two partners ( 7 , 74 ). However, in agreement to the results obtained with MLV where 20% of particles were found containing viral RNA ( 80 ), these results indicate that the majority of the HIV viral particles lacks gRNA. These particles are not empty because they contain cellular RNAs ( 30 , 33 , 71 , 81 ).…”
Section: Discussionsupporting
confidence: 91%
“…It remains to be determined if MoMuLV or other retroviruses utilizes heterogeneous transcriptional start site usage as a means of controlling transcript dimerization, as appears to be the case for HIV-1. Interestingly, more than 40 years ago, Levin and Rosenak proposed that MuLV-producing cells likely contain two non-interconverting pools of viral transcripts that function separately as viral mRNA and gRNA, based on the sensitivity of gRNA incorporation into virions produced in the presence of the transcription inhibitor, actinomycin D [ 406 ], and more recently Mougel et al showed that nuclear export of MuLV gRNA and mRNAs occurs via different pathways [ 407 ]. Although HIV evolved a Rev-dependent mechanism to promote nuclear export [ 408 ], it remains plausible that the evolutionarily distant HIV and MoMuLV retroviruses could both utilize heterogenous transcriptional start site usage as a means of producing distinct pools of messenger and genomic RNA transcripts.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Moreover, it has been shown that this nuclear export is dependent on some particular components of the TREX1 complex: While spliced MLV mRNAs require the UAP56 helicase for export, unspliced genomic mRNAs instead depend on THOC5, THOC7, and the splice factor SRp20 [ 175 , 176 ]. Recent work showed that MLV RNAs are exported through both the CRM1 and NXF1 pathways, with the CRM1 pathway priming exported unspliced RNAs for packaging [ 177 ]. This further proves that nuclear export mechanisms can influence the downstream fate of viral RNAs.…”
Section: Nuclear Export Of Viral Mrnasmentioning
confidence: 99%